What are the barriers that discourage young mothers from continuing breastfeeding following hospital discharge? A grounded theory study - Burton, Martha (2014)
Abstract Breastfeeding is widely recognised as the method of infant feeding that provides the greatest health benefits for mother and child (World Health Organisation, 2003). Despite the benefits of breastfeeding, among young mothers (under 20) the prevalence of breastfeeding remains significantly lower than the national average. 57% of young mothers who elect to breastfeed discontinue during the early postpartum period (6-8 weeks) and by six months only 11% of young mothers are breastfeeding (Office National Statistics, 2012). In the UK, young motherhood is associated with social exclusion and domestic violence (Beers and Hollo, 2009; ONS, 2012). Young mothers are more likely to engage in negative health behaviours such as smoking and are less likely to access antenatal care (Department of Health, 2008). The combined consequences of these factors increase the risk of poor maternal and infant health, notably an infant mortality rate 60% higher than among older mothers (DH, 2008). For these reasons, current healthcare policy has identified the promotion of breastfeeding among young mothers as a key strategy in reducing health inequalities (DH, 2012). Within this study, individual interviews were conducted with eight young mothers in order to explore the lived experience of breastfeeding. Concurrent data collection and analysis were conducted following the principle of Classic Grounded Theory (Glaser and Strauss, 1967). The study findings highlight the diverse experiences of young mothers who elect to breastfeed and the barriers to accessing support services. The process of constant comparative analysis led to the development of three core categories: barriers to breastfeeding, overcoming barriers and the transition from breastfeeding to formula feeding. These findings are explored in light of relevant literature and the implications for nursing and midwifery practice are discussed. Recommendations for future practice include: raising the public profile of breastfeeding, promoting antenatal education and improving postnatal support for young mothers.